OS01.5.A Neuron-specific enolase (NSE) and S100 serum levels in patients with active brain metastases from HER2-positive breast cancer treated with trastuzumab-deruxtecan (T-DXd): A biomarker analysis from the TUXEDO-1 trial. (5th September 2022) - Berghoff, A S; Bartsch, R; Furtner, J; Marhold, M; Bergen, E S; Roider-Schur, S; Starzer, A M; Forstner, H; Rottenmanner, B; Dieckmann, K; Bago-Horvath, Z; Widhalm, G; et al.
Abstract: Background: T-DXd is a novel antibody-drug conjugate with high activity in HER2-positive metastatic breast cancer. The prospective, single-arm, single-centre phase II TUXEDO-1 trial showed clinically relevant activity of T-DXd in HER2-positive BC pts with active BM with an intracranial response rate of 73.3%. This biomarker sub-study of TUXEDO-1 aimed to investigate changes in the extent of metastases-induced brain damage in patients with and without response to therapy by measuring the serum levels of two proteins constitutively expressed in the human brain and measurable upon brain damage in the blood serum: NSE and S100. Material and Methods: We assessed serum NSE (sNSE) and serum S100 (sS100) levels in a total of 37 blood samples drawn at cycles 1, 4 and end of treatment (EOT) in all patients of the intent-to-treat population of the TUXEDO-1 trial using commercially available ELISA assays. Intracranial radiological response was centrally assessed by a board-certified neuro-radiologist using RANO criteria. sNSE and sS100 levels were compared between responders and non-responders using the Mann Whitney U test and a significance level of 0.05. Results: At baseline, we detected no significant difference of sNSE or sS100 levels between T-DXd responders and non-responders, respectively. Baseline median sNSE level was 10.6 ng/ml (interquartile range (IQR) 8.6-12.2) in T-DXd responders as compared with median 12.5 ng/ml (IQR 12.2-12.9) in the non-responder group (n.s.). At cycle 4, corresponding numbers were 8.1 ng/ml in responding patients (IQR 7-11.2) and 12.7 ng/ml (IQR 12.2-12.9) in non-responders, respectively ( p =0.009). No differences in sS100 levels were observed between the groups at any time point. Conclusion: In patients showing intracranial objective response to T-Dxd, sNSE levels were significantly lower at cycle 4 as compared with non-responders, suggesting a reduction in metastases-induced brain damage as a direct treatment effect. sNSE may be a clinically useful biomarker for longitudinal assessment of brain metastasis burden.